Pengaruh Waktu Belajar dan Minat Belajar terhadap Hasil Belajar Matematika - Indah Lestari (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
The purpose of this research was to the determinate the effect of study time on mathematics learning outcomes. To determinate the effect of interest in earning the mathematics learning outcomes. To determinate the effect of the interaction between study time and interest in learning the mathematics learning outcomes. Methods of research used survey methods expose facto. Sample of 52 people selected at random from all junior high school students in the district Cipayung. Data collection is done by giving a written test questions to measure variables studied. Data analysis using descriptive statistics and 2-way anova. the results showed the significant effect of study time on mathematics learning outcomes with sig = 0,038. There is significant effect of interest in learning the mathematics learning outcomes with sig – 0,00. There is no significant effect of the interaction between study time and interest in learning the mathematics learning outcomes with sig = 0,422.